Pascal Boyer: Den ganske historie om religion (nogensinde) - Jensen, Jeppe Sinding (Religionsvidenskabeligt tidsskrift, 2003)
This review article was occasioned by the publication of Pascal Boyer’s Religion Explained. The Evolutionary Origins of Religious Thought (2001), the title of which left this reviewer in some doubt and intent on investigating whether Boyer’s ambition has been fulfilled. Here, it must be noted that this reviewer is generally positive about the rewarding aspects of the ‘cognitive turn’ in the study of religion and Boyer’s earlier substantial contributions to this, but he is also wary of the fallacy of ‘partial explanation’: explaining a part does not amount to an explanation of the whole.After a presentation of the reviewer’s perspective and involvement in a research group working on religious narrative, cognition and culture, a substantial step-by-step review of the contents and structure of Boyer’s argument is presented. Then follows a discussion of the central concepts of domain specificity concerning cognitive representations and the ‘counter-intuitive’ nature of religious thought and, further, Boyer’s subsequent ideas concerning rituals and the ramifications for social formations and historical developments in what he calls ‘The Full History of All Religion (ever)’. Next, the reviewer offers some ‘critical intuitions’ and questions the return of (a new mode of) psychologism in the human sciences and Boyer’s dependence upon earlier theorizing which is not clearly noted nor acknowledged, but which has consequences for the epistemic status of his project and for those who follow the same tracks in the cognitive study of religion. It turns out that the methodology is based on extreme individualistic and scientistic attitudes, where ‘higher-order’ theoretical objects are explained (away?) by lower-order phenomena. In short, Boyer (and others) stops where culture begins and, as a consequence, religion is transformed into an epiphenomenal category without any causal effects. In the chosen theoretical perspective, religions ‘mean’ nothing; there exist ‘nothing but’ the cognitive representations of individual individuals - but in this manner, the currently dominating approach in the cognitive study of religion perpetuates a Cartesian mystique and a dubious physicalist dualism concerning the mind and the objects it ‘cognizes’. Cognitive theory is definitely an advance in the study of religion but it takes more than materialist fideism to make it convincing. The work of language, culture etc. has to be accounted for more seriously and in more detail.